Refuge or Resource: Home and Nostalgia in Postsocialist Estonia - Anu Kannike (Journal of Ethnology and Folkloristics)
The focus of this article is on nostalgia as it appears in the representations of home-decoration in postsocialist Estonia. This theme is explored, describing a dialogue and conflict between different versions of relating to the past. The empirical material comprises qualitatively analysed in-depth interviews and articles in home-decoration journals from 1997–2008. Examining some dimensions and mechanisms of nostalgia in this specific context enables to demonstrate how is transformation from Soviet everyday culture into Western consumer culture conceptualised through ideas about the home. I will suggest that in Estonian everyday life nostalgia is not only a form of escapism into the past from the uncertain present and identity problems, but it also works as a resource to cope with the traumatic past, negotiate and forge new identities.